PROSES DIVERSI DALAM SISTEM PERADILAN ANAK SEBAGAI UPAYA PEMBINAAN ANAK YANG MELAKUKAN TINDAK PIDANA - Adnyaswari Sudewa, Desak Made; Tuni Cakabawa L., Putu (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013)
The paper is titled "The Divertion Process in The Criminal Justice System Child Development Effot For Children Who Do Crime". This paper is used the methods of normatvr juridical and legislative approach. Chils as stipulated in article 1 of law number 23 year 2002 on Child Protection is a person who are under 18 of age, including children who are still in the worm.
Keywords: Children, divertion process, criminal justice system